Cover Picture: Phosphinothiolates as Ligands for Polyhydrido Copper Nanoclusters (Chem. Eur. J. 49/2014). Issue 49 (1st December 2014) - Huertos, Miguel A.; Cano, Israel; Bandeira, Nuno A. G.; Benet‐Buchholz, Jordi; Bo, Carles; van Leeuwen, Piet W. N. M.
<x xml:space="preserve">Abstract</x> The peculiar structure of the nanocluster, reported by P. W. N. M. van Leeuwen et al. in their Full Paper on page 16121 ff., consists of eighteen copper atoms and ten phosphinothiolate anions with a core of eight copper atoms, four additional atoms sticking out via bridging ligands, and on top and below the central core three atoms also glued to the cluster via bridging ligand interactions. The structure of the cluster is unusually "unorganized" compared to most other clusters, although it does have an inversion center.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>